Intra-personal Conflict Strategies - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Evidence suggests the process of decision-making itself—in addition to the final outcome—has important implications for households. This tool, Intra-personal Conflict Strategies, aims to deepen our understanding of how decisions are made when spouses have different preferences or constraints. When household members agree on the decision (regardless of the motivations), the decision-making process is relatively simple to understand. But when differences in opinions arise, the intrahousehold decision-making process can be more complex. It is important to understand differences in intra-personal conflict styles and how these differences impact the decision-making outcomes within the household. This tool uses vignettes aimed to capture five potential conflict strategies in which individuals may engage (avoidance, dominance, compromise, obliging, and collaboration). The vignettes build on Rahim ’s (1983) Model of Conflict Management styles for interpersonal conflicts, which is widely used to assess conflict behavior of individuals across five styles: (1) Avoidance, (2) Dominance, (3) Compromise, (4) Obliging, and (5) Collaboration. This information could be used to develop appropriate interventions that recognize the various types of conflict strategies people in a given area use within household decision-making. It may also be used to characterize household types for further analysis. This data study includes following files. 1. A survey document (including implementation guidelines)